EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Hotmaida Lestari Siregar; Yulia Pratiwi Siregar; Lukman Hakim Siregar (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to describe the effectiveness of using flipped classroom learning model on the ability to understand students' mathematical concepts on the topic Phytagoras theorem at the eighth grade students of SMP Negeri 8 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 25 students as the sample and they were taken by using cluster sampling technique from 226 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using flipped classroom was 3.80 (good category) and (b) the average of the ability to understand students' mathematical concepts on the topic Phytagoras theorem before using AIR learning model was 68.00 (enough category) and after using AIR learning model was 87.00 (very good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22), the result showed the significant value was less than 0.05 (0.000<0.05). It means, using AIR was effective used on the ability to understand students' mathematical concepts on the topic Phytagoras theorem at the eighth grade students of SMP Negeri 8 Padangsidimpuan.